Evaluating Changes in the Transmission Mechanism of Government Spending Shocks - Rebei, Nooman (IMF Working Papers; Working Paper, 2017)
We empirically revisit the crowding-in effect of government spending on private consumption based on rolling windows of U.S. data. Results show that in earlier samples government spending is increasingly crowding in private consumption; however, this relation is reverted in the latest periods. We propose a model embedding non-separable public and private consumption in the utility function and rule-of-thumb consumers to assess the sources of non-monotonic changes in the transmission of the shock. The iterative full information estimation of the model reveals that changes in the co-movement between private and public spending is primarily driven by the fluctuations in the elasticity of substitution between private and public consumption, the share of financially constrained consumers, and the elasticity of intertemporal substitution.